Malawi [in Strategies and priorities for African agriculture] - Benin, Samuel; Thurlow, James; Diao, Xinshen; McCool, Christen; Simtowe, Franklin (International Food Policy Research Institute, 2012)
During 2000–06, Malawi’s agricultural sector was one of the worst performing in Sub-Saharan Africa, with its gross domestic product (GDP) declining by an average 0.6 percent per year (World Bank 2010). Given that agriculture constituted more than one-third of Malawi’s economy, its stagnation slowed overall economic growth in the country, despite nonagriculture’s stronger performance. Population growth also outpaced economic growth, causing per capita incomes to fall. By 2006 Malawi and its agricultural sector were clearly in crisis. Poverty remained high and widespread, and malnutrition and food insecurity were worsening (Malawi, NSO 2005; Harrigan 2008).